Emotional, behavioural problems and cigarette smoking in adolescence: findings of a Greek cross-sectional study - Rotsika Vasiliki; Kolaitis Gerasimos; Dimitrakaki Christine; Tzavara Chara; Giannakopoulos George; Tountas Yannis (BMC, 2010)
Abstract Background Although several studies have reported findings concerning the association between smoking and emotional/behavioural problems, little research has investigated this association after controlling for confounding factors which have been found to be significantly correlated with both cigarette smoking and emotional/behavioural problems and may have a strong effect on the relationship between adolescents' mental health and smoking. The present study attempted to assess the association between adolescents' smoking status and their emotional/behavioural problems after controlling for a number of possible confounders (i.e. age, gender, parental smoking status, exposure to family smoking, family socioeconomic status, adolescents' leisure time) in a Greek nation-wide school-based sample. Methods Participants completed a questionnaire which retrieved information about age, gender, family socioeconomic status, smoking status, parental smoking, adolescents' leisure time and emotional/behavioural problems. Data were modelled using multiple logistic regression analysis with adolescents' smoking status as the dependent variable. Results A total of 1194 (i.e. 63% response rate) of self-reported questionnaires (40.1% boys, 59.9% girls; 12-18 years old) were returned. Data from 1030 participants with full data were analyzed. Cigarette smoking was strongly associated with higher levels of emotional/behavioural problems (p < 0.001) and the association was not moderated (OR = 1.13, 95% CI: 1.08-1.18) after controlling for the effects of other covariates. Emotional symptoms, conduct problems and hyperactivity/inattention were all significantly associated with adolescents' current smoking. Conclusions This study supports the association between smoking and emotional/behavioural problems among adolescents. Addressing adolescents' needs regarding their emotional/behavioural health could be helpful in the development of effective anti-smoking strategies in school environment and elsewhere.